PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN EKONOMI DI SMA SWASTA KAMPUS NOMMENSEN TAHUN AJARAN 2023/2024 - Christina Futi Kasih Zega; Anton Luvi Siahaan; Debbi Petra Meyana Sitorus (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research focuses on the use of the NHT learning model on the learning outcomes of grade X students in Economics subjects. The objectives to be achieved in this study are to determine the improvement of learning outcomes in students by applying the NHT cooperative learning model and comparing the effect of learning outcomes using the NHT cooperative learning model with the learning outcomes of students using lecture learning.The research method used was a quasi-experimental design method using descriptive statistics. The data collection method was carried out using one experimental group and one control group, the experimental group was given a pre-test and treatment with learning using the NHT model, after which a post-test was given. Then with a different class, the control group was given a pre-test and treatment with learning using the lecture method, after which a post-test was given. The participants in this study were two classes, including the experimental class in class X1 and the control class in class X3.The results showed that there was an effect of student learning outcomes, on the learning model used in the teaching and learning process can be seen in the learning outcomes of students who used the NHT model, had a completeness value of 75.5 and in the control class that used the lecture method of 60.4.